Political representation of ethnic minorities and socio-demographic groups in the Romanian parliament - Matichescu, Marius Lupşa (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The paper explores the effects that different institutional mechanisms for legislative representation have on ethnic and social diversity in national legislatures. It uses an original data set on the Romanian parliament between 1990 and 2016 to examine representational outcomes generated by a combination of specific types of electoral mechanisms such as list proportional representation and reserved seats. The paper's findings highlight potential adverse effects that the use of communal representation mechanisms can have on the ethnic inclusiveness of main political parties. The findings also point to substantial differences in the social profile of representatives elected through different institutional channels.
Keywords: Romania; Romunija; narodne manjšine; parlamenti; politično predstavništvo; družbeni profil; sprava